ANALISIS PERUBAHAN TINGGI MUKA AIR LAUT DI KOTA PADANG TAHUN 2008 SAMPAI 2012 DENGAN MENGGUNAKAN DATA PERMANENT SERVICE FOR MEAN SEA LEVEL (PSMSL) - , MUKTI FATIMAH, Ir. Dr. Istarno, Dipl., LIS.,M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Global sea level rise in the last century was approximately 20 cm with 3 mm average per year. The rise is followed by regional and local sea level rise that affects directly to the coast area. The fact is so many people ( Â± 23% of people) in the world, live in coast area. Therefore, monitoring of sea level changes and defining the external factors of the change are needed. This research will analyze the change of Mean Sea Level during five years and the external factors of sea level changes in Padang City by using Permanent Service for Mean Sea Level (PSMSL) Station data. Sea level data can be calculated to define monthly MSL and annualy MSL that has been corrected with spike error, missing data, and shifting correction previously. Monthly MSL and annualy MSL which are calculated by T-Tide or Microsoft Excel is used to analyze sea level change in Padang City. Meteorology data, consist of precipitation and rain intensity, are needed to define the external factors of sea level change. Linier regression is used as the model of analysis. The result shows that annualy MSL for five years is not significantly different with +5,8 mm total or +1,8 mm change in per year. Rain intensity and precipitation do not influence the annualy or monthly sea level change. MSL, precipitation and rain intensity in the end of the year are higher. Earthquake and flood make the daily MSL is higher than the monthly MSL.